Variation in Meristic Characters of four strains of Malaysian Freshwater Angelfish Pterophyllum scalare (L.) - Elizabeth Koshy, Bibi; Selvaraj, Oyyan; Sekaran, Muniandy (Malaysian Journal of Science, 2008)
The present study conducted between 2002 and 2006 to determine the strains of Pterophyllum sealare (freshwater angelfish) available in the ornamental fish trade of Malaysia indicated that there are 46 strains present including the long-fin strains. Four strain of this fish were studied for phenotypic variation based on their meristic counts. Significant variation in counts of pelvic fin rays, anal fin rays, caudal fin rays and dorsal fill rays were observed among the strains.